THE ANALYSIS OF THE AARHUS CONVENTION IN THE CONTEXT OF GOOD ENVIRONMENTAL GOVERNANCE - Počuča, Milan Bogdan; Mladenov, Marijana; Mirković, Predrag (Economics of Agriculture, 2018)
The purpose of this article is to examine mechanisms for public involvement in environmental governance from the perspective of the Aarhus Convention. Analysis method explained the connection between the basic postulates included in the Aarhus Convention and the main principles of good governance in environmental matters. Normative methods presented the provisions of the Aarhus Convention related to the right to an adequate environment and rights of access to information, public participation, and equal access to justice. By using the same method, the special attention was devoted to the transposition and implementation of the requirements of the Convention into the legal system of the Republic of Serbia. Through the case study research method, the authors examined the relevant practice of the Compliance Committee. Authors conclude that transposition of the requirements of the Aarhus Convention represents a valuable contribution in establishing good environmental governance.